Multidisciplinary Organizational and Legal, Forensic and Pharmaceutical, Medical and Immunological Researches in The Organization and Management of Pharmaceutical Competencies During the Circulation of Drugs in The Relief of Alcoholic Addiction - Chuiev, Yurii; Konovalova, Lyudmyla (SSP Modern Pharmacy and Medicine, 2022)
During the circulation of drugs within the multidisciplinary organizational and legal, forensic and pharmaceutical, medical and immunological researches in the organization and management of pharmaceutical competencies, a comparative analysis of the cost of pharmacotherapy in the relief of alcoholism to determine the most cost-effective treatment regimen. Two modern schemes of pharmacotherapy for relief of drunken forms of alcohol dependence were developed. During the circulation of medicines, eleven drugs were selected for the main group and ten drugs for the control group. Organized a comparative analysis of the cost of basic pharmacotherapy in the relief of alcoholic dependence to determine the most cost-effective treatment regimen. Found that the cost of the basic pharmacotherapy scheme for the experimental group of patients is 40% cheaper than the basic pharmacotherapy scheme for the control group. It was established that the scheme of the course of pharmacotherapy in the relief of alcoholic addictions for the research group is more effective, safer, economical and has fewer side effects on the patient's body.